If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(2x+5)+x+2=-11
We move all terms to the left:
-(2x+5)+x+2-(-11)=0
We add all the numbers together, and all the variables
x-(2x+5)+13=0
We get rid of parentheses
x-2x-5+13=0
We add all the numbers together, and all the variables
-1x+8=0
We move all terms containing x to the left, all other terms to the right
-x=-8
x=-8/-1
x=+8
| -4(2x-9)+6(-x+1)=8x-5(3x-3) | | 2w+-10=2 | | x+3/11=2/3 | | 4.11-2m=2(4–m) | | 24=3/4(x+7) | | 11x55=121 | | 8=w+255 | | /0.25x-12=18-0.55x | | p-65/5=6 | | 3/4m=6.5 | | 1/2(w+2)=5 | | | | | | | | | | | | | | | | | | 2+7y=3-3y | | | | | | | | | | | | | | | | | | | | | | | | |